Impact of a Dietary Citrus Extract on the Behavior and Production of Lactating Dairy Cows Following Regrouping: A Preliminary Study - Padua, Felipe H.; Dancy, Kaitlyn M.; Bergeron, Renée; DeVries, Trevor J. (Frontiers in Veterinary Science, 2022)
Exposure of lab animals, humans, and pigs to olfactory sensory feed additives may reduce response to stress and anxiety. The objective of this preliminary study was to determine if feeding a citrus-based olfactory sensory functional feed extract (derived from Citrus sinensis) reduces the negative impact of regrouping of lactating dairy cows. Thirty-two (parity =2.0±1.2; mean±SD), mid-lactation Holstein dairy cows (169.8±16.8 DIM) were enrolled as focal cows in and housed individually in a tie-stall facility where they were randomly assigned to 1 of 2 treatment diets: 1) control total mixed ration (control; n=16; primiparous=7; multiparous=9), or 2) control total mixed ration with 4 g/d of citrus extract (Phodé, Terssac, France) (CE; n=16; primiparous=7; multiparous=9). Cows were fed their experimental diets for 7 d in the tie-stall facility (baseline), then moved to 1 of 2 experimental free-stall pens (containing 29 other cows) for a 7-d period, where they remained on the same treatment diet. Compared to baseline, primiparous control cows had decreased rumination time on d 1 and 2, had decreased lying time on d 1, and tended to have decreased lying time on d 2 and 3 following regrouping. Primiparous CE cows had greater feeding time on d 1 and tended to have greater feeding time on d 2 after regrouping compared to primiparous control cows. Primiparous control cows had greater idle standing time, as compared to the CE cows, across the 7 d after regrouping. Primiparous CE cows initiated less total competitive behavior after regrouping, but were also displaced more frequently from the feed bunk and from the free stalls on d 1 after regrouping, as compared to the primiparous control cows. For multiparous cows, CE supplementation was not consistently associated with any benefits to behavior or production after regrouping, possibly because these cows were more experienced with social stressors. Results indicate that feeding CE to mid-lactation naïve primiparous dairy cows may reduce the initiation of competitive interactions and lessen the reduction in rumination and lying time after regrouping. These results need to be verified in further studies where potential confounding effects (e.g. pen social dynamics, pen location) are minimized.